Peculiarities of Information support in the Interior Troops of the Interior Ministry of Ukraine - Dovbnya, V. V. (Honor and Law, 2019)
Requirements to the data to be analyzed in command and control agencies of the Interior Troops are determined. Means of obtaining data and information sources as well as possible data that can be further obtained from these sources are analysed.